Factors influencing self-management for preventing recurrent stroke attacks among patients at the stroke foundation clinic in Bali, Indonesia, 2023 - Ni Luh Putu Thrisna Dewi; I Made Kariasa; A.A Istri Dalem Hana Yundari; Ni Made Diah Pusparini Pendet; I Gede Juanamasta (Kashan University of Medical Sciences, 2024)
Background: Effective self-management practices post-stroke have been shown to decrease mortality rates and enhance the quality of life for patients. While existing studies have explored various factors impacting self-management, further investigation is necessary to identify key determinants that influence self-management and aid in preventing recurrent strokes.Objectives: This study aims to identify the factors that influence self-management among stroke survivors to prevent recurrent attacks.Methods: A cross-sectional study was conducted in April 2023 a stroke foundation in Bali, Indonesia, involving 116 post-stroke patients recruited through non-probability consecutive sampling. Data collection utilized the Stroke Self-Management Questionnaire, with analysis performed using chi-square and logistic regression methods.Results: Gender and age did not exhibit significant associations with self-management. However, regression analysis revealed that education (P=0.002, OR=2.136), previous stroke history (P<0.001, OR=4.122), and pre-existing medical conditions (P=0.011, OR=7.151) were significantly correlated with self-management.Conclusion: The study highlights the significance of education level, prior stroke experience, and comorbid conditions as influential factors affecting self-management and the likelihood of recurrent stroke attacks. Understanding these determinants is crucial for designing tailored interventions and support systems to enhance self-management practices in stroke patients.